Characterization of LysBC17, a Lytic Endopeptidase from Bacillus cereus - Steven M. Swift; Irina V. Etobayeva; Kevin P. Reid; Jerel J. Waters; Brian B. Oakley; David M. Donovan; Daniel C. Nelson (MDPI AG, 2019)
Bacillus cereus, a Gram-positive bacterium, is an agent of food poisoning. B. cereus is closely related to Bacillus anthracis, a deadly pathogen for humans, and Bacillus thuringenesis, an insect pathogen. Due to the growing prevalence of antibiotic resistance in bacteria, alternative antimicrobials are needed. One such alternative is peptidoglycan hydrolase enzymes, which can lyse Gram-positive bacteria when exposed externally. A bioinformatic search for bacteriolytic enzymes led to the discovery of a gene encoding an endolysin-like endopeptidase, LysBC17, which was then cloned from the genome of B. cereus strain Bc17. This gene is also present in the B. cereus ATCC 14579 genome. The gene for LysBC17 encodes a protein of 281 amino acids. Recombinant LysBC17 was expressed and purified from E. coli. Optimal lytic activity against B. cereus occurred between pH 7.0 and 8.0, and in the absence of NaCl. The LysBC17 enzyme had lytic activity against strains of B. cereus, B. anthracis, and other Bacillus species.